1993
DOI: 10.1007/bf00037274
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from leaf discs of peanut and pigeonpea: Influence of benzyladenine, indoleacetic acid and indoleacetic acid-amino acid conjugates

Abstract: The influence of indoleacetic acid (IAA) and some IAA-amino acid conjugates in combination with benzyladenine (BA) on in vitro shoot regeneration from leaf discs of peanut and pigeonpea was investigated. The frequency of shoot regeneration and average number of shoot buds produced was dependent on the type of auxin present in the medium. Highest frequency of plant regeneration in peanut was induced by BA in combination with IAA or IAA-l-alanine, while in pigeonpea BA in combination with IAA or IAA-l-aspartic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 15 publications
4
32
1
1
Order By: Relevance
“…Katsumi and Kazama (1978) reported enhanced auxin biosynthesis by supplementation of GA3, which may become occasionally toxic for growth and shoot elongation (Soetikno 1981). Eapen and George (1993) obtained regeneration of calli from the leaf discs of pigeon pea and peanut, and indicated that BAP + IAA or IAA + aspartic acid are essential for shoot bud elongation. In addition, Kumar et al (1983) reported regeneration from the leaf callus of pigeon pea on Blaydes (1966) medium with 0.5 mg L −1 BAP, 0.1 mg L −1 NAA, and 0.01 mg L −1 GA3.…”
Section: Shoot Bud Elongationmentioning
confidence: 99%
“…Katsumi and Kazama (1978) reported enhanced auxin biosynthesis by supplementation of GA3, which may become occasionally toxic for growth and shoot elongation (Soetikno 1981). Eapen and George (1993) obtained regeneration of calli from the leaf discs of pigeon pea and peanut, and indicated that BAP + IAA or IAA + aspartic acid are essential for shoot bud elongation. In addition, Kumar et al (1983) reported regeneration from the leaf callus of pigeon pea on Blaydes (1966) medium with 0.5 mg L −1 BAP, 0.1 mg L −1 NAA, and 0.01 mg L −1 GA3.…”
Section: Shoot Bud Elongationmentioning
confidence: 99%
“…BAP and GA 3 each 0.5 mg l −1 showed optimum elongation of the regenerated shoots. Earlier workers reported the successful elongation of regenerated shoots with application of BAP and IAA together (Eapen and George 1993). However, GA 3 alone or in combination with BAP and IAA also elongated micro-shoots (Dayal et al 2003;Eapen et al 1998;Villiers et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Another effect of amino acids in the tissue culture is the synergic effect with the plant growth regulators, as found in pigeonpea and peanut. In the peanut, the highest frequency of plant regeneration was induced by the BAP in combination with IAA or IAA-lalanine, while in pigeonpea, the BAP in combination with IAA or IAA-l-aspartic acid produced best results (Eapen and George 1993).…”
Section: Amino Acidsmentioning
confidence: 95%